Aesthetic experiences with young children in Hong Kong - Ho, C.K.L. (Meaning making in early childhood research: Pedagogies and the personal, 2018)

Artificial intelligence and forensic computing - Lobo-Marques, J. Al (Forensic Computing, 2018)

Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices: A case study with Macao-Chinese girls - Correia, Ana; Fernandes, Clara; Maia, João (Beyong mirrors: Research pathways (CeiDE 2013-2017), 2018)

Beyong Mirrors: Research Pathways (CeiDE 2013-2017) (Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices: A case study with Macao-Chinese girls., 2018)

Concordância verbal - Baxter, A. N.; Lopes, N. (Tânia Lobo (ed.) O português escrito por afro-brasileiros no século XIX: atas de reuniões da Sociedade Protetora dos Desvalidos, 2018)

Creating multiculturalism amidst ethnic, linguistic and religious diversity: a Filipino perspective. - Monera, Arnold (Multiculturalism in Asia – Peace and Harmony, 2018)

Education for justice-oriented and participatory citizenship in a politicized era in Hong Kong. (Handbook of Research on Education for Participative Citizenship and Global Prosperity, 2018)

Inquérito aos estudantes da Universidade de São José: o peso da cultura na aprendizagem das línguas - Espadinha, M. A.; Borges, V. (A framework in Portuguese as a Foreign Language for Chinese Native Speakers, 2018)

Investigating the urban rulesof the Pearl River Delta: a comparative approach to urban design research and teaching - Tieben, H.; Soares, Nuno; Yiu, E. (IN-TERSECTIONS. Expertise, AcademicResearch and Design from Barcelona, Beirut, Hong Kong, Brisbane, Auckland, Florence, 2018)

Macau entre a ‘China Tropical’ e a Lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Novas perspetivas sobre o luso-tropicalismo, Portuguese Studies Review PSR, 2018)

Obediência militar, liberdade e consciência, Ética Aplicada: Política, Edições 70, - Carreiras, H.; Leandro, F. J. (2018)

Portuguese as an Additional Language: Domains Use among Young Learners - Neves, Ana Cristina (Language Policy and Language Acquisition Planning, 2018)
Three key concepts will make up the pillars of this paper: second, foreign and heritage languages. Whenever appropriate “additional language” will be used as an umbrella term. A study of the domains of language use will be applied to these three different sociolinguistic contexts. To date, there are not many empirical studies on the domains of language and, more specifically, among young learners in different areal contexts, as it is the case of this study.
Keywords: Additional language; Domains of language use; Foreign language; Heritage language; Language policy; Second language

The OBOR geopolitical drive: the Chinese access security Strategy - Leandro, Francisco J. B. S. (The Belt and Road Initiative Law, Economics, and Politics, 2018)

The OBOR Global Geopolitical Drive: The Chinese Access Security Strategy - - Leandro, F. J (Law, Economics, and Politics, 2018)